Synergistic Combination of Citrus Flavanones as Strong Antioxidant and COX-Inhibitor Agent - Antonella Smeriglio; Nunzio Iraci; Marcella Denaro; Giuseppina Mandalari; Salvatore Vincenzo Giofrè; Domenico Trombetta (MDPI AG, 2023)
Recently, we demonstrated that a Citrus flavanone mix (FM) shows antioxidant and anti-inflammatory activity, even after gastro-duodenal digestion (DFM). The aim of this study was to investigate the possible involvement of the cyclooxygenases (COXs) in the anti-inflammatory activity previously detected, using a human COX inhibitor screening assay, molecular modeling studies, and PGE2 release by Caco-2 cells stimulated with IL-1β and arachidonic acid. Furthermore, the ability to counteract pro-oxidative processes induced by IL-1β was evaluated by measuring four oxidative stress markers, namely, carbonylated proteins, thiobarbituric acid-reactive substances, reactive oxygen species, and reduced glutathione/oxidized glutathione ratio in Caco-2 cells. All flavonoids showed a strong inhibitory activity on COXs, confirmed by molecular modeling studies, with DFM, which showed the best and most synergistic activity on COX-2 (82.45% vs. 87.93% of nimesulide). These results were also corroborated by the cell-based assays. Indeed, DFM proves to be the most powerful anti-inflammatory and antioxidant agent reducing, synergistically and in a statistically significant manner (p < 0.05), PGE2 release than the oxidative stress markers, also with respect to the nimesulide and trolox used as reference compounds. This leads to the hypothesis that FM could be an excellent antioxidant and COX inhibitor candidate to counteract intestinal inflammation.